Debates sobre la república en El Quiteño Libre. Cultura política e impresos (1833-1834) (Estudios) - Castro Lagos, Roger Eliacer (2023)
This article analyzes the Republic foundation promoted by the El Quiteño Libre’s editor team. In each of its issues, the journal questioned the actions of President Juan José Flores and simultaneously exposed arguments that show the editors’ thoughts and allow us to identify the way of conceiving the Republic for an independent Ecuador, different from the one being built under Flores’ mandate. The article identifies the people behind the publications, describes the materiality of El Quiteño Libre, and analyzes the debates raised by the journal between the years 1833-1834.